Ownership structure and financing behavior of listed firms in consumer product sector in Malaysia - Kiing, Hui Ching (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study aims to examine the relationship between ownership structure and financing behavior of Malaysia listed firm for consumer product sector. The study covers the period 2005 to 2009 for firm level data for 68 selected non-financial firms from consumer product sector which were listed under Bursa Malaysia Berhad. Multivariate regression analysis was being employed in this study for examines the influence of ownership structure on the firm's financing decision (debt-equity ratio). Ownership Structure of the firm was represented by managerial shareholding. Negative relationship was found between managerial shareholding and debt-equity ratio (capital structure). Beside that corporate governance variables such as board size and the presence of non-executive directors in the board were also been take into consideration in this study. Positive relationship between corporate governance variables and debt-equity ratio has been found. Lastly, control variables which represented by sales growth, profitability and liquidity were also applied in this study. Negative relation was found between these control variables and firm's debt equity ratio. Finding of this study is in line with the theories, such as agency theory and pecking order theory.